RESEARCHING COMFORT CRITERIA IN THE PROGRAM OF DEVELOPED TERRITORIES RENOVATION - Alexey E. Fokin (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article puts forward the approach to designing the indicator of dwelling comfort. The author studies the procedure of demolishing houses of the 1st period of industrial house-building and models processes of developed territories renovation. Variants of reconstruction projects are discussed, which take into account the overseas experience and possible sources of finance. The author identifies the most important criteria of dwelling comfort through conducting a survey in the form of group questioning. The findings were analyzed. On the basis of the research a model for finding the maximum efficiency of using developed territories liable for renovation was designed.